Chemical-dynamic polishing of semiconductor materials based on Bi and Sb chalcogenides by using HNO₃–HCl solutions - Pavlovich, I.I.; Tomashik, Z.F.; Stratiychuk, I.B.; Tomashik, V.M.; Savchuk, O.A.; Kravtsova, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The chemical etching of Ві₂Те₃ and n-(Ві₂Те₃)₀.₉(Sb₂Te₃)₀.₀₅(Sb₂Se₃)0.05 and p- (Bi₂Te₃)₀.₂₅(Sb₂Te₃)₀.₇₂(Sb₂Se₃)₀.₀₃ crystals of solid solutions with HNO₃–HCl etchant compositions was investigated. The dependences of dissolution rate of these semiconductors on etchant composition, stirring, temperature and their shelf-time storage have been studied. It was shown that the process of dissolution of the investigated materials in the polishing solutions HNO₃–HCl is limited by the diffusion stages.